2023
DOI: 10.1183/20734735.0267-2022
|View full text |Cite
|
Sign up to set email alerts
|

Current and future developments in the pharmacology of asthma and COPD: ERS seminar, Naples 2022

Abstract: Pharmacological management of airway obstructive diseases is a fast-evolving field. Several advances in unravelling disease mechanisms as well as intracellular and molecular pathways of drug action have been accomplished. While the clinical translation and implementation ofin vitroresults to the bedside remains challenging, advances in comprehending the mechanisms of respiratory medication are expected to assist clinicians and scientists in identifying meaningful read-outs and designing clinical studies. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 115 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…16,17 GCs resistance caused by HDAC2 activity decreases, dysfunction of corticosteroid glucocorticoid receptor-α and GR-β increases in epithelial cells, etc., may be a reason why COPD patients cannot benefit from GC treatment. [18][19][20] Recent studies have shown that microRNAs are associated with GCs resistance in COPD. 21 MicroRNAs (miRNAs) are a kind of noncoding single-stranded RNA that are conserved and widely distributed in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 GCs resistance caused by HDAC2 activity decreases, dysfunction of corticosteroid glucocorticoid receptor-α and GR-β increases in epithelial cells, etc., may be a reason why COPD patients cannot benefit from GC treatment. [18][19][20] Recent studies have shown that microRNAs are associated with GCs resistance in COPD. 21 MicroRNAs (miRNAs) are a kind of noncoding single-stranded RNA that are conserved and widely distributed in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%